ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN PONSEL NOKIA - Herawati, Wiwik (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2004)
The aim of study is to analyze the impact of atittude , perception and need on customer prefferention of nokia hand phone users in Surabaya. When analyze on opinion of 100 samples from population with accidental sampling technique and questionairre as tools for collecting the data, this study shows that there are significance impacts of atittude , perception and need on customer prefferention of Nokia's handphone.